The Effect of Financial Literacy on Economics Teachers’ Investment Behavior: The Mediating Role of Financial Attitude and Its Implications for Social Studies Learning - Basuki Pramono; Yola Yolanda; Roza Sri Susanti; Aulia Apriani (SOSEARCH : Social Science Educational Research, 2026)
Abstract This study aims to examine the effect of financial literacy on the investment behavior of economics teachers, analyze the influence of financial literacy on financial attitude, and investigate the mediating role of financial attitude in the relationship between financial literacy and investment behavior, as well as its implications for Social Studies (IPS) learning. This study employed a quantitative approach with an explanatory research design. Data were collected through a survey using a structured questionnaire administered to 128 senior high school economics teachers in Kampar Regency, selected purposively from a population of 135 teachers. The instrument measured financial literacy, financial attitude, and investment behavior using eight indicators for each variable on a five-point Likert scale. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS software. The results indicate that financial literacy has a positive and significant effect on financial attitude (β = 0.722; p < 0.001) and investment behavior (β = 0.298; p < 0.01). Financial attitude also has a positive and significant effect on investment behavior (β = 0.516; p < 0.001) and acts as a partial mediator in the relationship between financial literacy and investment behavior. The coefficient of determination shows that financial literacy explains 52.1% of the variance in financial attitude (R² = 0.521), while financial literacy and financial attitude jointly explain 63.7% of the variance in investment behavior (R² = 0.637). These findings suggest that financial literacy not only enhances teachers’ financial management capabilities but also contributes to strengthening financial literacy education in Social Studies (IPS) learning through teachers’ practical financial experiences.